2016
DOI: 10.1038/ncomms10811
|View full text |Cite
|
Sign up to set email alerts
|

BTG2 bridges PABPC1 RNA-binding domains and CAF1 deadenylase to control cell proliferation

Abstract: While BTG2 plays an important role in cellular differentiation and cancer, its precise molecular function remains unclear. BTG2 interacts with CAF1 deadenylase through its APRO domain, a defining feature of BTG/Tob factors. Our previous experiments revealed that expression of BTG2 promoted mRNA poly(A) tail shortening through an undefined mechanism. Here we report that the APRO domain of BTG2 interacts directly with the first RRM domain of the poly(A)-binding protein PABPC1. Moreover, PABPC1 RRM and BTG2 APRO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
84
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 66 publications
11
84
0
1
Order By: Relevance
“…The role of Tis21 in the cell proliferation control has been recently associated in human cells to RNA deadenylation, by which it influences mRNA poly(A) tail shortening (Stupfler et al, 2016). Nevertheless, in Set A we detect the deregulation of genes related to AS or to NMD, but not to mRNA deadenylation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Tis21 in the cell proliferation control has been recently associated in human cells to RNA deadenylation, by which it influences mRNA poly(A) tail shortening (Stupfler et al, 2016). Nevertheless, in Set A we detect the deregulation of genes related to AS or to NMD, but not to mRNA deadenylation.…”
Section: Discussionmentioning
confidence: 99%
“…Co-immunoprecipitation (Co-IP) assays in human embryonic kidney 293 (HEK293) cells confirmed the interaction between TTR and PABPC1 ( Figure 2A); in hRECs, western blot analysis indicated that PABPC1 levels increased with TTR, while lncRNA-MEG3 overexpression or knockdown showed no significant effects on the PABPC1 level with TTR ( Figure 2B) in high-glucose environments. Previous studies demonstrated that PABPC1 participates in regulation pathways and lncRNA stabilization [33][34][35]. To investigate whether PABPC1 regulated the stability of lncRNA-MEG3, actinomycin D was used to inhibit RNA synthesis in hRECs.…”
Section: Ttr Interacted With Poly(a) Binding Protein Cytoplasmic 1 (Pmentioning
confidence: 99%
“…In our previous work using miRNA microarray and qRT-PCR assays, miR223-3p was upregulated in serum and aqueous humor of DR patients, and TTR was proved to affect neovascularization in DR through the STAT4/miR-223-3p/FBXW7 signaling pathway [32]. However, how lncRNA-MEG3 interacts with TTR in DR remains to be explored.As the interaction between lncRNA-MEG3 and miR223-3p has been reported in human aortic endothelial cells (HAECs) [30], in the current study we aim to investigate: (1) the potential relationship between TTR and lncRNA-MEG3; and (2) the relationship between lncRNA-MEG3 and poly(A) binding protein cytoplasmic 1 (PABPC1), on the basis that the co-immunoprecipitator, PABPC1, has been identified as the direct binding target of TTR and has been reported to bind the poly (A) tails of mRNAs, regulating the stability and biofunction of lncRNAs [33][34][35],.This study was designed to elucidate the details of the interactions between TTR and miR223-3p, including the potential direct targets of TTR (PABPC1) and miR223-3p (lncRNA-MEG3) in DR, both in vivo and in vitro, which might provide new principles on the molecular pathogenesis, clinical prevention, and therapy of DR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This generates RNA regulatory networks, structured such that a single protein can regulate the expression of numerous genes (Joshi et al, 2011;Keene, 2007;Lapointe et al, 2017; Understanding the molecular basis of accelerated deadenylation has been limited by the lack of a biochemical system containing purified components that reconstitutes this process. Previous studies have shown that a purified domain of the budding yeast Pumilio protein Mpt5 stimulates the activity of immunoprecipitated Ccr4-Not (Goldstrohm et al, 2006), and that isolated Caf1 is stimulated by addition of purified BTG2 and PABPC1 (Stupfler et al, 2016). We recently purified the complete seven-subunit S. pombe Ccr4-Not complex after overexpression of the subunits in insect cells (Stowell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%